1985
DOI: 10.1113/jphysiol.1985.sp015733
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose levels modulate efferent activity in the vagal supply to the rat liver.

Abstract: SUMMARY1. Efferent discharges were recorded from nerve filaments dissected from the hepatic branch of the vagus nerve in the rat.2. Intravenous administration of D-glucose enhanced efferent activity in the hepatic branch of the vagus nerve, whereas 2-deoxyglucose and insulin suppressed this activity.3. The rate at which these fibres fire was found to be related to the concentration of glucose in the blood.4. Vagal hepatic nerve activity was effectively blocked by section of the left cervical vagus indicating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 16 publications
2
29
0
1
Order By: Relevance
“…When the hepatic branch of the vagus nerve is excised, icv insulin administration-induced suppression of HGP is attenuated [27]. The vagus nerve is known to maintain constant pacemaker-like activity [33], and it has been reported in an electrophysiological study of the rat under pentobarbital anesthesia that the nerve activity is enhanced by a rise in blood glucose, and inactivated by an increase in plasma insulin concentration [34]. However, the question of how the central insulin action actually controls the vagus nerve activity via hypothalamic neurons and suppresses HGP remains unanswered.…”
Section: Central Insulin Action and The Vagus Nervementioning
confidence: 99%
“…When the hepatic branch of the vagus nerve is excised, icv insulin administration-induced suppression of HGP is attenuated [27]. The vagus nerve is known to maintain constant pacemaker-like activity [33], and it has been reported in an electrophysiological study of the rat under pentobarbital anesthesia that the nerve activity is enhanced by a rise in blood glucose, and inactivated by an increase in plasma insulin concentration [34]. However, the question of how the central insulin action actually controls the vagus nerve activity via hypothalamic neurons and suppresses HGP remains unanswered.…”
Section: Central Insulin Action and The Vagus Nervementioning
confidence: 99%
“…Electrical stimulation of the lower portion of the cut end of the vagus nerve increased hepatic glycogen synthase activity and deposition of glycogen and decreased net hepatic glucose output in rabbits (15). Niijima (16) demonstrated that intravenous injection of glucose increased the efferent ®ring rate in the hepatic branch of the vagus nerve in rats, and that the ®ring rate was directly related to the arterial blood glucose concentration over a range of physiologic concentrations (3.3±25.0 mmol/l). On the other hand, sympathetic stimulation was shown to activate glycogen phosphorylase and glucose-6-phosphatase (G-6-Pase) in rabbits (17) and to deplete hepatic glycogen reserves and increase net hepatic glucose output in calves (18).…”
Section: Autoregulation In Response To Hyperglycemiamentioning
confidence: 99%
“…As hyperglycemia enhances glycogen synthesis in the liver [28], these results also suggest that the glycogen synthesis in the liver might be stimulated via vagi. NIuIMA [46] reported that i.v. injection of glucose increased efferent activity in the hepatic branch of the vagus nerve in the rat, the firing rate of hepatic efferents being linearly related to the arterial blood glucose concentration over a range from 60 mg/100 ml to 450 mg/ 100 ml, which includes the physiological range.…”
Section: Innervation Of the Liver And Its Role In Thementioning
confidence: 99%
“…The effect of 2-deoxy-D-glucose could be accounted for by inhibition of intracellular glucose utilization in the brain [10,66]. These observations indicate that changes in the rate of hepatic glycogenesis, which occur in response to change in blood glucose concentration, are mediated in part by the vagal efferent Innervation of the liver [46]. It is recognized that there are two centers in the hypothalamus regulating food intake, the feeding center in the lateral hypothalamus (LHA) and the satiety center in the ventromedial hypothalamus (VMH) [2,4].…”
Section: Innervation Of the Liver And Its Role In Thementioning
confidence: 99%